From medical school to global health leadership: 35-year career outcomes and gender disparities from the Aga Khan University Medical College - Adil H. Haider; Maham Vaqar; Asma Altaf Hussain Merchant; Sharjeel Ahmad; Komal Abdul Rahim; Namra Qadeer Shaikh; Noreen Afzal; Shayan Shah; Anum Rahim; Saad Bin Zafar Mahmood; Saqib Kamran Bakhshi; Sadaf Khan; et al. (BMC Medical Education)
Abstract Background Medical education plays significant role in shaping the future of healthcare, and understanding the career outcomes of medical graduates provides valuable insights into the effectiveness of educational programs. With no published data using alumni surveys in the South Asian region, we set out to conduct a survey to gain insights into the career trajectories, professional milestones, and accomplishments of 35 graduating classes from one of Pakistan’s largest Academic Medical Centers (AMC). Methods An online survey was distributed to 2,177 alumni of the Aga Khan University (AKU), Pakistan who graduated from 1988 to 2021. This cross-sectional survey explored graduates’ higher education, training, practice settings, and four key outcomes: awards, leadership roles, research impact, and contributions to healthcare and educational innovations. A multipronged approach leveraging outreach from leadership, social media engagement, peer-to-peer appeals, event-based promotion, and targeted text reminders to maximize survey participation was employed. Data were analyzed using descriptive statistics, chi-square tests for association, and multivariable logistic and multinomial regression to assess independent predictors of career outcomes. Results 1,201 alumni (55.2%) responded to the survey, demonstrating the effectiveness of this multifaceted approach. After the exclusion of missing data, 862 responses were analyzed. Both genders were equally represented (49.8%). Most participants had completed residency (82.0%) and fellowship (56.0%) training. Nearly half (48.5%) were employed in an academic setting. A proportion (57.7%) of alumni had received awards, and nearly one-third of the respondents (31.6%) were involved in developing healthcare or educational innovations. Over half of the respondents (53.7%) had served in leadership roles, and a number had been involved in research (68.9%), with 18.6% receiving grant funding. While an overwhelming 95% of female respondents were employed, they had lower odds of serving in a leadership role and research involvement than their male counterparts. Conclusion The findings of this study serve as a testament to the effectiveness of AKU’s educational programs in preparing graduates to make significant contributions to healthcare and society. Continuous quality improvement initiatives, fostering a culture of giving back within its alumni, and creating opportunities for females through diverse endeavors can pave the way for sustained and heightened accomplishments among its graduates.